Effect of HBx on inflammation and mitochondrial oxidative stress in mouse hepatocytes - Ling, Li-Rong (Oncol Lett, 2020)
Hepatitis B virus × protein (HBx) serves an important role in the pathogenesis of the hepatitis B virus infection. Previous studies have reported that the interaction between HBx and hepatocyte mitochondria is an important factor leading to liver cell injury and apoptosis, ultimately inducing the formation of liver cancer. In the present study, a mouse model expressing HBx was constructed using hydrodynamic in vivo transfection based on the interaction between HBx and cytochrome c oxidase (COX) subunit III. The specific mechanism of HBx-induced oxidative stress in mouse hepatocytes and the subsequent effect on mitochondrial function and inflammatory injury was assessed. The results demonstrated that HBx reduced the activity of COX and the expression of superoxide dismutase and upregulated the expression of malondialdehyde, NF-κB and phospho-AKT, thus increasing oxidative stress. In addition, HBx induced an increase in interleukin (IL)-6, IL-1β and IL-18 expression levels, which created an inflammatory microenvironment in the liver, further promoting hepatocyte inflammatory injury. Therefore, it was proposed that HBx may affect hepatocyte mitochondrial respiration by reducing the activity of cytochrome c oxidase, leading to mitochondrial dysfunction and inducing hepatocyte inflammation and injury.